Cathode active materials for rechargeable lithium-ion batteries
A lithium-ion rechargeable battery active material with specific compositions and crystalline structure enhances discharge capacity, reduces irreversible capacity, and lowers internal resistance, addressing existing performance issues.
Patent Information
- Application Number
- JP2023536164
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-15
- Filing Date
- 2021-12-14
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-12-14
AI Technical Summary
Existing positive electrode active materials for lithium-ion rechargeable batteries exhibit low initial discharge capacity (DQ1), high irreversible capacity (IRRQ), and high internal resistance (DCR at 50% SOC).
A positive electrode active material comprising Li, M', where M' is Ni with a content of 60.0 to 75.0 mol%, Co with 0.0 to 20.0 mol%, Mn with 0.0 to 35.0 mol%, and D with 0.0 to 2.0 mol% (D being Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, Zn, or Zr), with Al, B, and W totaling 0.1 to 5.0 mol%, and having specific atomic ratios and crystalline structure, is developed.
The new material achieves higher DQ1, lower IRRQ, and lower DCR at 50% SOC, improving the electrochemical performance of lithium-ion rechargeable batteries.
Smart Images

Figure 0007620107000010 
Figure 0007620107000011 
Figure 0007620107000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a particulate active cathode material for lithium-ion rechargeable batteries. More particularly, the present invention relates to a particulate active cathode material comprising Al, B and W elements, a battery comprising the particulate active cathode material comprising Al and B elements, and the use of the particulate active cathode material in a battery in any one of a portable computer, a tablet, a mobile phone, an electric vehicle and an energy storage system. [Background technology]
[0002] The present invention relates to a single crystal positive electrode active material powder for lithium-ion rechargeable batteries (LIBs), comprising the elements Al, B and W.
[0003] A positive electrode active material containing Al and B elements is already known, for example, from US Patent Application Publication No. 2016 / 336595. In US Patent Application Publication No. 2016 / 336595, a positive electrode active material powder is prepared by mixing lithium nickel manganese cobalt oxide (NMC) and Al(OH). 3 Powder and B 2 O 3 It is disclosed that the positive electrode active material contains a mixture of NMC and a powder, followed by heating at 400° C. The Ni content in NMC is about 60 mol%. However, the positive electrode active material according to US Patent Application Publication No. 2016 / 336595 has a low initial discharge capacity (DQ1), a high irreversible capacity (IRRQ), and a high internal resistance (DCR at SOC 50%). Summary of the Invention [Problem to be solved by the invention]
[0004] It is therefore an object of the present invention to provide a positive electrode active material having improved electrochemical properties, for example, one or more of the following DQ1, IRRQ and DCR at SOC 50%: [Means for solving the problem]
[0005] This object is achieved by providing a cathode active material for a lithium ion rechargeable battery, the cathode active material being a powder, the cathode active material comprising Li, M′ and oxygen, M′ being: Ni with a content a of 60.0 mol% to 75.0 mol% relative to M'; Co with a content x of 0.0 mol% to 20.0 mol% relative to M'; Mn with a content y of 0.0 mol% to 35.0 mol% relative to M'; D having a content z of 0.0 mol% to 2.0 mol% relative to M', D including at least one element selected from the group consisting of Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, Zn and Zr; Al, B, and W, wherein the total content c of Al, B, and W is 0.1 mol% to 5.0 mol% relative to M'; a, x, y, z and c are measured by ICP; a+x+y+c+z is 100.0 mol%, The positive electrode active material is Al content AI A , B content B A and W content W A Al A , B A and W A was measured by ICP analysis, and Al A , B A and W A is expressed as a mole fraction compared to the sum of a, x, and y, The powder has an average Al fraction of Al, as determined by XPS analysis. B , average B fraction B B and the average W fraction W B indicates Al B , B B and W B is expressed as a mole fraction compared to the sum of the Co, Mn and Ni fractions as determined by XPS analysis, Relative Al B / Al A > 1.0, Ratio B B / B A > 1.0, ratio W B / W A > 1.0, The powder is a single crystal powder.
[0006] It is indeed observed that higher DQ1, lower IRRQ and lower DCR at SOC 50% are achieved using the cathode active material according to the present invention, as shown by the examples and supported by the results provided in Tables 3 and 4.
[0007] The present invention further provides an electrochemical cell comprising an active cathode material according to the first aspect of the invention, and the use of an active cathode material according to the first aspect of the invention in a battery.
[0008] By way of further guidance and to better understand the teachings of the present invention, drawings are included which are intended to aid in the explanation of the invention and are not intended to limit the invention disclosed herein. [Brief description of the drawings]
[0009] [Figure 1a] 1 shows a Scanning Electron Microscope (SEM) image of a positive electrode active material powder according to EX (Example) 1 having a single crystal morphology. [Figure 1b] 1 shows a scanning electron microscope (SEM) image of the positive electrode active material powder from EX2 having a single crystal morphology. [Figure 2a] A comparison of the discharge DCR at -10°C for CEX (comparative) 1.1, CEX1.2 and EX1 as a function of the state of charge in % is shown. [Figure 2b] 1 shows a comparison of discharge DCR at −10° C. for CEX2.1, CEX2.2 and EX2 as a function of state of charge in %. [Figure 3a]The XPS spectrum of EX2 measured in the range of 66-80 eV including the Al2p and Ni3p peaks is shown. [Figure 3b] The XPS spectrum of EX2 measured in the range of 187 to 197 eV, including the B1s peak, is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Unless otherwise defined, all terms used in disclosing the present invention, including technical and scientific terms, have the meanings commonly understood by those skilled in the art to which the present invention belongs. With further guidance, definitions of terms are included to better understand the teachings of the present invention. As used herein, the following terms have the following meanings: The term "ppm" as used herein means parts per million by mass.
[0011] As used herein, "about" referring to a measurable value such as a parameter, amount, length of time, and the like, is meant to encompass a variation of no more than ±20%, preferably no more than ±10%, more preferably no more than ±5%, even more preferably no more than ±1%, and even more preferably no more than ±0.1% from the specified value, provided such variations are appropriate for the practice of the disclosed invention, although it is to be understood that the value to which the "about" modifier refers is itself specifically disclosed.
[0012] The recitation of numerical ranges by endpoints includes not only the recited endpoints but also all values and fractions subsumed within that range. All percentages are to be understood as percentages by weight, abbreviated as "wt. %," unless otherwise defined or a different meaning is apparent to one of ordinary skill in the art from their usage and in the context in which they are used.
[0013] The term "median particle size D50" as defined herein may be used interchangeably with the terms "D50" or "d50" or "median particle size" or "median particle size (d50 or D50)". D50 is defined herein as the particle size at 50% of the cumulative volume percent distribution. D50 is typically measured by laser diffraction particle size analysis.
[0014] As defined herein, the term "at%" is equivalent to the term "atomic percent" and indicates atomic percentage. The term "at%" in a concentration expression of a given element means what percentage of all atoms in the compound involved are atoms of that element. The term "at%" is equivalent to the term "mol%" or "mole percent".
[0015] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode, which is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a certain period of time.
[0016] positive electrode active material In a first aspect, the present invention provides an active cathode material for a lithium ion rechargeable battery, the active cathode material being a powder, the active cathode material comprising Li, M′ and oxygen, M′ being Ni with a content a of 60.0 mol% to 75.0 mol% relative to M'; Co with a content x of 0.0 mol% to 20.0 mol% relative to M'; Mn with a content y of 0.0 mol% to 35.0 mol% relative to M'; D having a content z of 0.0 mol% to 2.0 mol% relative to M', D including at least one element selected from the group consisting of Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, Zn and Zr; Al, B, and W, wherein the total content c of Al, B, and W is 0.1 mol% to 5.0 mol% relative to M'; a, x, y, z and c are measured by ICP; a+x+y+c+z is 100.0 mol%, The positive electrode active material is Al content AI A , B content B A and W content W A With AI A , B A and W A is measured by ICP analysis, and the AI A , B A and W A is expressed as a mole fraction compared to the sum of a, x, and y, The powder has an average Al fraction of Al, as determined by XPS analysis. B , average B fraction B B and the average W fraction W B indicates Al B , B B and W B is expressed as a mole fraction compared to the sum of the Co, Mn and Ni fractions as determined by XPS analysis, AI B / AI A >1.0, and the ratio B B / B A >1.0, and the ratio W B / W A > 1.0, The powder is a single crystal powder.
[0017] The single crystal powder has a size of at least 45 μm by at least 60 μm (i.e., at least 2700 μm) in the SEM image. 2 ), preferably at least 100 μm x 100 μm (i.e., at least 10,000 μm 2 ) is considered to be a powder in which 80% or more of the powder particles within the field of view have a single crystal morphology.
[0018] A particle is considered to have a single crystal morphology if it consists of only one grain or a very small number of constituent grains, up to five, as viewed by SEM or TEM. For example, particles with single crystal morphology are shown in Figures 1a and 1b, which are SEM images of EX1 and EX2, respectively.
[0019] For the measurement of the single crystal morphology of particles, grains having a maximum linear dimension observed by SEM that is smaller than 20% of the median particle size D50 of the powder as measured by laser diffraction are ignored. This avoids inadvertently considering grains that are essentially single crystal but may have several other very small grains deposited on them as not having single crystal morphology.
[0020] The positive electrode active material for lithium-ion rechargeable batteries according to the present invention has indeed improved electrochemical properties when used in electrochemical cells, and can achieve higher DQ1, lower IRRQ and lower DCR at SOC50%, as illustrated by the examples and results shown in Table 3.
[0021] The XPS analysis provides the atomic content of elements in the top layer of the positive electrode active material particle at a penetration depth of about 10 nm from the outer edge of the particle, also referred to as the "surface."
[0022] The composition of the positive electrode active material particles is expressed by the general formula Li according to the stoichiometry of elements measured by known analytical methods such as ICP-OES (inductively coupled plasma optical emission spectrometry, hereinafter also referred to as ICP) and IC (ion chromatography). 1 +b(Ni a Mn y CO x A c D z ) 1-b O 2 The ICP analysis provides the weight fraction of elements in the positive electrode active material particles.
[0023] Preferably, the positive electrode active material has a nickel content, a, relative to M', of at least 62.0 mol %, more preferably at least 64.0 mol %, as measured by ICP.
[0024] Preferably, the cathode active material has a cobalt content x relative to M' of at least 0.0 mol%, 1.0 mol%, at least 2.0 mol%, or even at least 3.0 mol%, as measured by ICP. The invention provides an cathode active material having a cobalt content x relative to M' of 0.0, 3.0, 5.0, 7.0, 9.0, or 10.0 mol%, or any value therebetween, as measured by ICP. In a preferred embodiment, the cathode active material has a cobalt content x relative to M' of 0.0 mol% to 2.0 mol%, as measured by ICP.
[0025] Preferably, the cathode active material has a manganese content, y, relative to M', of at most 35.0 mol%, preferably at most 30.0 mol%, as measured by ICP. Preferably, the cathode active material has a manganese content, y, relative to M', of at least 10.0 mol%, at least 12.0 mol%, or even at least 15.0 mol%, as measured by ICP. The invention provides cathode active materials having a manganese content, y, relative to M', of 15.0, 20.0, 25.0, or 30.0 mol%, or any value therebetween, as measured by ICP.
[0026] Preferably, the present invention provides an active cathode material having a molar ratio of lithium to the total molar amount of nickel, manganese and / or cobalt of 0.95≦Li:Me≦1.10, where Me is the total molar fraction of Ni, Mn and / or Co.
[0027] Preferably, the present invention provides a positive electrode active material according to the first aspect of the present invention, wherein the particles contain Al, B and W. When measured by ICP, the total content of Al, B and W relative to M' is preferably 0.1 to 5.0 mol %, more preferably 0.4 to 2.0 mol %.
[0028] Preferably, Al A is 0.025-2.0 mol %, as measured by ICP, and is expressed as a mole fraction relative to the sum of a, x, and y.
[0029] Preferably, B A is 0.025-2.0 mol %, as measured by ICP, and is expressed as a mole fraction relative to the sum of a, x, and y.
[0030] Preferably, W A is 0.025-2.0 mol %, as measured by ICP, and is expressed as a mole fraction relative to the sum of a, x, and y.
[0031] Preferably, as measured by ICP, A is at least 0.0015, in other words at least 0.15 mol %, more preferably B A is at least 0.0018, in other words at least 0.18 mol %, expressed as a mole fraction compared to the sum of a, x and y.
[0032] Preferably, Al A is at most 0.0080, in other words at most 0.8 mol %, as measured by ICP, expressed as a mole fraction compared to the sum of a, x and y.
[0033] Preferably, W A is less than 0.002, in other words less than 0.2 mol %, as measured by ICP, and is expressed as a mole fraction compared to the sum of a, x and y.
[0034] Preferably, the ratio Al B / Al A >10, more preferably Al B / Al A >150.
[0035] In a preferred embodiment, the ratio Al B / Al A <800.
[0036] Preferably, the ratio B B / B A >10, more preferably ratio B B / B A>30, most preferably ratio B B / B A >115.
[0037] In a preferred embodiment, the ratio B B / B A <500.
[0038] Preferably, the ratio W B / W A >10, more preferably ratio W B / W A >50, most preferably ratio W B / W A >115.
[0039] In a preferred embodiment, the ratio W B / W A <500.
[0040] Preferably, the positive electrode active material has a median particle size (d50 or D50) of 2.0 μm to 9.0 μm as measured by laser diffraction. The median particle size (d50 or D50) can be measured using a Malvern Mastersizer 3000. Preferably, the median particle size is 2.0 μm to 8.0 μm, more preferably 3.0 μm to 7.0 μm, and most preferably about 4.0 μm.
[0041] It is indeed observed that the positive electrode active material according to the present invention achieves the objective of providing higher DQ1, lower IRRQ and lower DCR at SOC50% when used in an electrochemical cell, as illustrated by the examples and supported by the results provided in Tables 3 and 4.
[0042] DQ1 and IRRQ are measured by a coin cell test procedure using a 1C current definition of 160 mA / g in the 4.4-3.0 V / Li metal window range, and the DCR at SOC50% is measured by a full cell test procedure using a 1C current definition of 2000 mAh / g at −10° C. The test procedures are further described in § 1.3 and are incorporated herein by reference.
[0043] Preferably, the positive electrode active material according to the first aspect of the present invention has a LiAlO 2 , Al 2 O 3 and Li-B-0 compounds.
[0044] Electrochemical Cell In a second aspect, the present invention provides a battery cell comprising an active cathode material according to the first aspect of the present invention.
[0045] In a third aspect, the present invention provides the use of the cathode active material according to the first aspect of the present invention in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system. EXAMPLES
[0046] The following examples are intended to further clarify the invention, but are not intended to limit the scope of the invention.
[0047] 1. Description of analysis method 1.1.Inductively Coupled Plasma The composition of the positive electrode active material powder is measured by an inductively coupled plasma (ICP) method using an Agilent 720 ICP-OES (Agilent Technologies, https: / / www.agilent.com / cs / library / brochures / 5990-6497EN%20720-725_ICP-OES_LR.pdf). One gram of powder sample is dissolved in 50 mL of high-purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with a watch glass and heated on a hot plate at 380 °C until the powder is completely dissolved. After cooling to room temperature, the solution from the Erlenmeyer flask is poured into a first 250 mL volumetric flask.
[0048] The first volumetric flask is then filled with deionized water up to the 250 mL mark, followed by a complete homogenization process (first dilution). An appropriate amount of solution is pipetted from the first volumetric flask and transferred to a second 250 mL volumetric flask for the second dilution, and the second volumetric flask is filled with internal standard elements and 10% hydrochloric acid up to the 250 mL mark, followed by homogenization. Finally, this solution is used for ICP measurement.
[0049] 1.2.Particle size distribution The particle size distribution (PSD) of the positive electrode active material powders is measured by laser diffraction particle size analysis using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory (https: / / www.malvernpanalytical.com / en / products / product-range / mastersizer-range / mastersizer-3000#overview) after dispersing each of the powder samples in an aqueous medium. Sufficient ultrasonic irradiation and stirring are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurement.
[0050] 1.3.Coin Cell Test 1.3.1. Preparation of Coin Cells 1.3.1.1.CEX1.1, CEX1.2, EX1, CEX2.1, CEX2.2 and EX2 For the preparation of the positive electrode, a slurry containing the positive electrode active material powder, conductor (Super P, Timcal), and binder (KF#9305, Kureha) in a solvent (NMP, Mitsubishi) in a weight ratio of 90:5:5 is prepared by a high-speed homogenizer. The homogenized slurry is spread onto one side of an aluminum foil using a doctor blade coater with a gap of 230 μm. The foil coated with the slurry is dried in an oven at 120° C. and then pressed with a gap of 40 μm using a calendar tool.
[0051] Then it is dried again in a vacuum oven to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard 2320) is placed between the positive electrode and the lithium foil as the negative electrode. 1M LiPF in EC / DMC (1:2) 6 is used as the electrolyte and dropped between the separator and the electrode, and the coin cell is then completely sealed to prevent leakage of the electrolyte.
[0052] 1.3.1.2.EX3.1 and EX3.2 For the preparation of the positive electrode, a slurry containing the positive electrode active material powder, conductor (Super P, Timcal), and binder (KF#9305, Kureha) in a solvent (NMP, Mitsubishi) with a weight ratio of 96.5:1.5:2.0 is prepared by a high-speed homogenizer. The homogenized slurry is spread on one side of an aluminum foil with a gap of 170 μm using a doctor blade coater. The foil coated with the slurry is dried in an oven at 120° C. and then pressed at a pressure of 530 bar using a hydraulic calendar tool.
[0053] Then it is dried again in a vacuum oven to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard 2320) is placed between the positive electrode and the lithium foil as the negative electrode. 1M LiPF in EC / DMC (1:2) 6 is used as the electrolyte and dropped between the separator and the electrode, and the coin cell is then completely sealed to prevent leakage of the electrolyte.
[0054] Test Method The test method is a conventional "fixed cutoff voltage" test. Conventional coin cell testing in this invention follows the schedule shown in Table 1. Each cell is cycled at 25°C using a Toscat-3100 computer controlled galvanostatic cycling station (Toyo, http: / / www.toyosystem.com / image / menu3 / toscat / TOSCAT-3100.pdf).
[0055] The 1C current definition is 160mAh / g. The initial charge capacity (CQ1) and discharge capacity (DQ1) are measured in constant current mode (CC) at a C-rate of 0.1C in the window range of 4.3V~3.0V / Li metal.
[0056] The irreversible capacity IRRQ is expressed as a percentage as follows:
[0057]
number
[0058] [Table 1]
[0059] Full Cell Test 1.3.3. Full cell preparation A 2000mAh (flexible) pouch-type cell is prepared as follows: Positive electrode active material powder, conductor (Super-P, Timcal (Imerys Graphite & Carbon)) as a conductive agent, graphite (KS6, Timrex (Imerys Graphite & Carbon), http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2014 / 04 / Powder-Metallurgy.pdf), and polyvinylidene fluoride (PVDF 1710, Kureha, https: / / www.kureha.co.jp / en / business / material / pdf / KFpolymer_BD_en.pdf) as a binder are added to N-methyl-2-pyrrolidone (NMP) as a dispersion medium, and the weight ratio of the positive electrode active material powder, conductive agent, and binder is 96 / 1 / 1 / 2. The mixture is then kneaded to prepare a mixed slurry. The resulting mixed slurry is then applied to both sides of a current collector made of aluminum foil with a thickness of 20 μm. The width of the applied area is 88.5 mm and the length is 425 mm. The typical loading weight of the positive electrode active material is about 16.9±0.2 mg / cm. 2 The electrode is then dried and a pressure of 4.5 Mpa is used to obtain an electrode density of 3.25±0.05 g / cm. 3 The positive electrode is then calendered to a temperature of 100° C. An aluminum plate is arc welded to the end of the positive electrode to serve as the cathode current collector tab.
[0060] A commercially available anode is used. Briefly, a mixture of graphite, carbon, carboxy-methyl-cellulose-sodium (CMC) and styrenebutadiene-rubber (SBR) in a weight ratio of 95 / 1 / 1.5 / 2.5 is applied to both sides of an 8 μm thick copper foil. A nickel plate is arc welded to the end of the anode, which acts as the anode current collector tab. The typical loading weight of the anode active material is 10±0.5 mg / cm. 2 It is.
[0061] Lithium hexafluorophosphate (LiPF ) was dissolved at a concentration of 1.2 mol / L in a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1 and 1% by volume of vinylene carbonate (VC). 6 ) salt to obtain a non-aqueous electrolyte. 2 F 2 An additive comprising:
[0062] To obtain a spirally wound electrode assembly, the positive electrode, the negative electrode, and a sheet of separator made of a 13 μm-thick microporous polymer film (Asahi Kasei) interposed therebetween were spirally wound using a winding core rod. The assembly and electrolyte were then placed in an aluminum laminated pouch in a dry room with a dew point of -50°C, thus preparing a flat pouch-type lithium rechargeable battery. The rechargeable battery has a design capacity of 2000 mAh when charged to 4.25 V. The non-aqueous electrolyte solution is impregnated at room temperature for 8 hours. The battery is precharged to 15% of its expected maximum capacity and aged at room temperature for 1 day. The battery is then degassed and the aluminum pouch is sealed. The battery is prepared for use as follows: the battery is charged in CC mode (constant current) using a current of 0.2C (1C=2000mA) up to 4.25V, then in CV mode (constant voltage) until a cutoff current of C / 20 is reached, and then discharged at a 0.2C rate in CC mode down to a cutoff voltage of 2.7V.
[0063] 1.3.4. Full cell test 1.3.4.1. Full cell cycle life test The prepared full-cell batteries are charged and discharged several times at 25° C. under the following conditions to measure their charge-discharge cycle performance: a. First charge is performed in CC mode at 1C rate up to 4.25V, then in CV mode until C / 20 is reached; b. The cell is then set to rest for 10 minutes; c. First discharge at 1C rate in CC mode down to 2.7V; d. The cell is then set to rest for 10 minutes; e. Charge-discharge cycling continues until the battery reaches approximately 80% retention capacity. After every 100 cycles, discharge once at 0.1C rate in CC mode down to 2.7V.
[0064] 1.3.4.2.Discharge DC resistance The internal resistance or direct current resistance (DCR) is measured by a pulse test suitable for the battery at -10°C as follows: a. First charge is performed in CC mode at 1C rate up to 4.25V, then in CV mode until C / 20 is reached; b. The cell is then set to rest for 10 minutes; c. First discharge at 1C rate in CC mode down to 90% SOC; d. The cell is then set to rest for 20 minutes; e. A second discharge is performed at a 1.5C rate for 10 seconds, followed by a 40 second rest; f. A second charge is performed at a 1.5C rate for 10 seconds, followed by a 1 minute rest; g. Repeat steps b through f in 10% intervals until an SOC of 10% is reached. Measure the DCR at each SOC level and compare the DCR at SOC 50%.
[0065] 1.4.X-ray photoelectron spectroscopy (XPS) In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In the XPS measurement, the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. Therefore, all elements measured by XPS are contained in the surface layer.
[0066] In the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Thermo K-α+ spectrometer (Thermo Scientific, https: / / www.thermofisher.com / order / catalog / product / IQLAADGAAFFACVMAHV).
[0067] Monochromatic Al Kα radiation (hυ=1486.6 eV) is used with a spot size of 400 μm and a measurement angle of 45°. A broad survey scan to identify the elements present at the surface is performed with a pass energy of 200 eV. The C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV is used as the calibration peak position after data collection. Then, for each identified element, at least 10 precise narrow scans at 50 eV are performed to determine the exact surface composition.
[0068] Curve fitting is performed using CasaXPS Version 2.3.19PR1.0 (Casa Software, http: / / www.casaxps.com / ) using Shirley-type background processing and Scofield sensitivity coefficients. Fitting parameters are from Table 2a. The lineshape GL(30) is a Gaussian / Lorentzian product formula with a 70% Gaussian line and a 30% Lorentzian line. LA(α,β,m) is the asymmetric lineshape, where α and β define the tail broadening of the peak and m defines the width.
[0069] [Table 2]
[0070] For the Al, Co and W peaks, constraints are set on the respective defined peaks according to Table 2b. Ni3p and W5p3 are not quantified.
[0071] [Table 3]
[0072] Table 2c shows the maximum peak intensity position range criteria for Al and B related compounds.
[0073] [Table 4]
[0074] *The range of binding energies of Al peak 1 varies with the amount of Al doped in the structure.
[0075] The surface contents of Al, B and W measured by XPS are expressed as the mole fraction of Al, B and W, respectively, in the surface layer of the particle divided by the total content of Ni, Mn and Co in said surface layer, which is calculated as follows:
[0076]
number
[0077] 2. Examples and Comparative Examples Comparative Example 1 A single crystalline positive electrode active material, labeled CEX1.1, is prepared according to the following steps: Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.68 Mn 0.27 Co 0.05 A nickel-based transition metal oxide hydroxide powder (TMH1) having the formula: is prepared by a co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.
[0078] Step 2) First Mix: TMH1 prepared in step 1) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal (Ni, Co and Mn) ratio of 1.03.
[0079] Step 3) First calcination: The first mixture from step 2) is calcined at 925° C. for 10 hours in an oxidizing atmosphere to obtain a first calcined powder, followed by air jet milling and sieving.
[0080] Step 4) Second mixing: The milled powders obtained from step 3) are mixed in an industrial blender with alumina powder (Al 2 O 3 ), each with respect to the total molar content of Ni, Mn and Co in the milled powder. 2 O 3 ) 500ppm Al, Co 3 O 4 2.0mol% Co, ZrO from powder 2 Mix with 0.25 mol % Zr from powder and 2.0 mol % Li from LiOH to obtain a second mixture.
[0081] Step 5) Second calcination: The second mixture from step 4) is calcined at 775° C. for 12 hours in an oxygen atmosphere to obtain a second calcined body.
[0082] Step 6) Grinding and sieving: The second calcined body from step 5) is ground and sieved together with alumina powder. The sieved powder containing 500 ppm Al has a median particle size of 4 μm as measured by laser diffraction measured on a Malvern Mastersizer 3000.
[0083] Step 7) Third Blend: The sieved powder from step 6) is mixed with H in an industrial blender. 3 BO 3 powder to obtain a third mixture containing 500 ppm B.
[0084] Step 8) Third calcination: The third mixture from step 7) is calcined at 375°C for 7 hours in an oxidizing atmosphere, followed by grinding and sieving with 500 ppm Al from alumina powder based on the total weight of the mixture from step 5). The product from this step is a ground powder labeled CEX1.1.
[0085] By air jet milling in step 3), CEX1.1 is a single crystal powder.
[0086] CEX1.1 is from US Patent Application Publication No. 2016 / 336595.
[0087] CEX1.2 is prepared according to the same method as CEX1.1, except that more H3BO3 powder is added in step 7) to obtain a third mixture containing 1000 ppm B.
[0088] Example 1 In step 7), EX1 3 Powder H 3 BO 3 A third mixture containing 500 ppm B and 2000 ppm W is prepared according to the same method as CEX1.1, except added together with the powder.
[0089] Comparative Example 2 A single crystalline positive electrode active material, labeled CEX2.1, is prepared according to the following steps: Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.73 Mn 0.20 Co 0.07 Nickel-based transition metal oxide hydroxide powder (TMH2) having the formula: is prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.
[0090] Step 2) First Mix: The TMH2 prepared in step 1) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal (Ni, Co and Mn) ratio of 1.00.
[0091] Step 3) First calcination: The first mixture from step 2) is calcined at 915° C. for 11 hours in an oxidizing atmosphere to obtain a first calcined powder.
[0092] Step 4) Wet bead milling: The first calcined powder from step 3) is bead milled in a solution containing 0.5 mol% Co relative to the total molar content of Ni, Mn and Co in the first calcined powder, followed by grinding and sieving processes to obtain a milled powder. The weight ratio of bead milling solid to solution is 65%.
[0093] Step 5) Second mixing: The milled powders obtained from step 4) are mixed in an industrial blender with 100% CO, 100% Mn ... 3 O 4 2.0mol% Co, ZrO from powder 2 Mix with 0.25 mol % Zr from powder and 8.5 mol % Li from LiOH to obtain a second mixture.
[0094] Step 6) Second calcination: The second mixture from step 5) is calcined at 775° C. for 12 hours in an oxygen atmosphere to obtain a second calcined body.
[0095] Step 7) Grinding and sieving: The second calcined body from step 6) is ground and sieved together with alumina powder to obtain a sieved powder. The sieved powder containing 500 ppm Al has a median particle size of 3.5 μm as measured by laser diffraction measured on a Malvern Mastersizer 3000.
[0096] Step 8) Third Blend: The sieved powder from step 7) is mixed with H in an industrial blender. 3 BO3 powder to obtain a third mixture containing 500 ppm B.
[0097] Step 9) Third Calcination: The third mixture from step 8) is calcined at 375°C for 7 hours in an oxidizing atmosphere, followed by grinding and sieving with 500 ppm Al from alumina powder based on the total weight of the mixture from step 9). The product from this step is a ground powder labeled CEX2.1.
[0098] By wet milling in step 4), CEX4.1 is a single crystal powder.
[0099] CEX2.2 is more H 3 BO 3 Prepare according to the same method as CEX2.1, except that powder is added in step 8), to obtain a third mixture containing 1000 ppm B.
[0100] Example 2 EX2 is WO in step 8). 3 Powder H 3 BO 3 A third mixture containing 500 ppm B and 2000 ppm W is obtained by preparing it according to the same method as CEX2.1, except adding them together with the powder.
[0101] Comparative Example 3 A single crystalline positive electrode active material, labeled CEX3, is prepared according to the following steps: Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.70 Mn 0.30 Nickel-based transition metal oxide hydroxide powder (TMH3) having the above structure is prepared by a co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First mixing: The TMH2 prepared in step 1) is mixed with LiOH and ZrO in an industrial blender. 2to obtain a first mixture having a lithium to metal (Ni, Co, and Mn) ratio of 1.05 and 1000 ppm Zr.
[0102] Step 3) First calcination: The first mixture from step 2) is calcined at 935° C. for 10 hours in an oxidizing atmosphere to obtain a first calcined powder.
[0103] Step 4) Wet bead milling: The first calcined powder from step 3) is bead milled, followed by grinding and sieving process to obtain milled powder. The weight ratio of bead milling solid to solution is 60%.
[0104] Step 5) Second calcination: The bead milled powder obtained from step 4) is heated in air at 775° C. for 12 hours to obtain the second calcined powder labeled as CEX3.
[0105] By wet milling in step 4), CEX3 is a single crystal powder.
[0106] Example 3 A single crystal positive electrode active material, labeled EX3, is prepared according to the following steps: Step 1) Mixing: CEX3 was mixed in an industrial blender with 100% Al, 100% Mn, and 100% Co, each based on the total molar content of Ni, Mn, and Co in CEX3. 2 O 3 250ppm Al, H from powder 3 BO 3 250 ppm B and WO from powder 3 Mix with 3000 ppm W from the powder to obtain a mixture.
[0107] Step 2) Calcination: The mixture from step 1) is calcined at 375°C for 8 hours in an oxygen atmosphere to obtain a calcined body. The product is ground and labeled as EX3.
[0108] [Table 5]
[0109] *Calculated by ICP measurement, M' is the total mole fraction of other elements as analyzed by ICP. na:No data
[0110] [Table 6]
[0111] [Table 7]
[0112] *Calculated relative to the total mole fraction of Ni, Mn and Co analyzed by ICP. **Calculated relative to the total mole fraction of Ni, Mn and Co analyzed by XPS.
[0113] Table 3 summarizes the compositions of the examples and comparative examples and their corresponding electrochemical properties. Comparison between CEX1.1 and CEX1.2 shows that the addition of extra B in CEX1.2 increases DQ1 slightly and decreases IRRQ, but at the same time increases the undesirable internal resistance indicated by high DCR at SOC 50%. Meanwhile, EX1, which has the same Ni / M' content as CEX1.1 and CEX1.2, demonstrates higher DQ1 and lower IRRQ in coin cell tests, lower DCR at SOC 50%, and better cycle life in full cell tests, indicating the necessity of the presence of W. Similarly, EX2, which has the same Ni / M' content as CEX2.1 and CEX2.2, demonstrates higher DQ1 and lower IRRQ in coin cell tests, and lower DCR at SOC 50% in full cell tests. 2a and 2b show the full discharge DCR measurements from SOC 10% to SOC 90%, with both EX1 and EX2 showing the lowest discharge DCR at all SOC% among the Ni / M′ groups of the examples and counterexamples.
[0114] Table 4 shows a comparison of electrochemical properties between CEX3 and EX3, both with 70:30 mol% Ni:Mn. EX3, which contains all of Al, B and W, shows improved electrochemical properties indicated by higher DQ1 and lower IRRQ.
[0115] The above Tables 3 and 4 show that the presence of Al, B and W in EX1, EX2 and EX3 is advantageous in improving the electrochemical properties of DQ1 and IRRQ of the positive electrode active material according to the present invention.
[0116] Table 5 summarizes the XPS analysis results of EX2 showing the fractions of Al, B and W relative to the total mole fractions of Ni, Mn and Co. Table 5 also compares with the ICP analysis results. A molar ratio higher than 1 suggests that the Al, B and W are enriched at the surface of the cathode active material, in relation to the XPS measurement where the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. On the other hand, the molar ratios of Al, B and W from the ICP measurement are obtained from the whole particle. Thus, an XPS to ICP ratio higher than 1 indicates that the elements Al, B or W are mainly present on the surface of the cathode active material. A ratio of XPS to ICP higher than 1 is observed for Al, B and W in EX2.
[0117] It is noted that due to the preparation method, EX1 also has a significantly higher than 1 ratio of Al, B and W abundances measured by XPS compared to those measured by ICP.
[0118] Furthermore, the XPS peak positions are associated with compounds originating from the preparation process. Figure 3a shows the Al peak of EX2 overlapping with the Ni3p peak, and Figure 3b shows the B1s peak of EX2. Peak deconvolution is performed to separate the contributions of each compound based on the peak position according to the criteria listed in Table 2c. The three different Al-containing compounds and the Ni3p contribution are separated in Figure 3a, and the results show that EX2 has Al on the surface. 2 O 3, LiAlO 2 and LiAl n Me 1-n O 2 In Figure 3b, the B1s peak is H 3 BO 3 The Li-BO compound is deconvoluted into a peak belonging to Li 2 B 4 O 7 and Li 4 B 2 O 5 It can be, but is not limited to,
Claims
1. 1. A cathode active material for a lithium ion rechargeable battery, the cathode active material being a powder, the cathode active material comprising Li, M′, and oxygen, where M′ is: Ni with a content a of 60.0 mol% to 75.0 mol% relative to M'; Co with a content x of 0.0 mol% to 20.0 mol% relative to M'; Mn with a content y of 0.0 mol % to 35.0 mol % relative to M'; D with a content z of 0.0 mol % to 2.0 mol % relative to M', D containing at least one element selected from the group consisting of Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, Zn and Zr; Al, B and W, wherein the total content c of Al, B and W is 0.1 mol % to 5.0 mol % relative to M'; a, x, y, z and c are measured by ICP; a+x+y+c+z is 100.0 mol%, The positive electrode active material has an Al content of AI A , B content B A and W content W A With AI A , B A and W A is measured by ICP analysis, AI A , B A and W A is expressed as a mole fraction compared to the sum of a, x, and y; The powder has an average Al fraction of Al, as determined by XPS analysis. B , average B fraction B B and the average W fraction W B and Al B , B B and W B is expressed as a mole fraction compared to the sum of the Co, Mn and Ni fractions as determined by XPS analysis, Ratio AI B / AI A > 1.0, Ratio B B / B A > 1.0, Ratio W B / W A > 1.0, The powder is a single crystal powder.
2. 2. The cathode active material of claim 1, wherein a is at least 62.0 mol %, or a is at least 64.0 mol %, relative to M', as measured by ICP.
3. Ratio of Al B / Al A >10, or the ratio Al B / Al A The positive electrode active material according to claim 1 or 2, wherein the molecular weight is >150.
4. Ratio AI B / AI A The positive electrode active material according to any one of claims 1 to 3, wherein the molecular weight is 800 or less.
5. Ratio B B / B A >10, or ratio B B / B A >30, or ratio B B / B A The positive electrode active material according to any one of claims 1 to 4, wherein the positive electrode active material is >115.
6. Ratio B B / B A The positive electrode active material according to any one of claims 1 to 5, wherein the molecular weight is 100 or less.
7. Ratio W B / W A >10, or the ratio W B / W A >50, or the ratio W B / W A The positive electrode active material according to any one of claims 1 to 6, wherein the positive electrode active material is >115.
8. Ratio W B / W A The positive electrode active material according to any one of claims 1 to 7, wherein Mn is less than 500.
9. The positive electrode active material according to any one of claims 1 to 8, wherein Co in the content x is 0.0 mol% to 2.0 mol% relative to M' as measured by ICP.
10. The positive electrode active material has a median particle size D50 of 2.0 μm to 7.0 μm as measured by laser diffraction particle size analysis. A The positive electrode active material according to any one of claims 1 to 9, comprising:
11. 11. The positive electrode active material according to claim 1, wherein M' comprises Al, B and W, each in an amount of at least 0.02 mol % relative to M', as measured by ICP.
12. A battery cell comprising the positive electrode active material according to any one of claims 1 to 11.
13. Use of the positive electrode active material according to any one of claims 1 to 11 in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.
Citation Information
Patent Citations
Lithium-ion secondary battery
JP2010118179A
Positive electrode for lithium secondary battery and lithium secondary battery using the same
JP2013093171A
Positive electrode active material particle for lithium ion secondary battery
JP2018092715A